Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/953612
|View full text |Cite
|
Sign up to set email alerts
|

Weakness and the Inability to Ambulate in a 14-Month-Old Female: A Case Report and Concise Review of Guillain-Barre Syndrome

Abstract: Guillain-Barre syndrome (GBS) is an acquired disease of the peripheral nervous system which causes demyelination and leads to weakness, ataxia, and areflexia. There are a variety of forms of the syndrome, and although it is found in all age groups, it is rare in children less than two years of age. The present complaint of weakness, ataxia, or lower extremity pain in the pediatric population should cause the practitioner to consider GBS in the differential. We describe a case of a 14-month-old girl presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…On the other hand, our findings of enhancement of the cauda equina on MRI, the albuminocytological dissociation in CSF, and evidence of demyelination on EMG, all supported a diagnosis of GBS. 3,5 It has been reported that GBS is a rare occurrence in young children 6 and recognizing it is more difficult and often delayed in preschool children, due to nonspecific presenting signs and a challenging neurological picture. 7 Ataxia may be the first sign of GBS in in young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our findings of enhancement of the cauda equina on MRI, the albuminocytological dissociation in CSF, and evidence of demyelination on EMG, all supported a diagnosis of GBS. 3,5 It has been reported that GBS is a rare occurrence in young children 6 and recognizing it is more difficult and often delayed in preschool children, due to nonspecific presenting signs and a challenging neurological picture. 7 Ataxia may be the first sign of GBS in in young children.…”
Section: Discussionmentioning
confidence: 99%
“…8 In most of the reported pediatric GBS cases, ataxia was described as an associated symptom to pain and progressive muscle weakness. 6,[8][9][10][11][12] When ataxia is the predominant clinical sign that is more often reported accompanied by ophthalmoplegia and areflexia, leading to the diagnosis of Miller-Fisher Syndrome (MFS). 13,14 In other cases, cranial nerve involvement and ataxia have been described as consistent with GBS syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…En sık görülen ise nonspesifik grip benzeri semptomları olan üst solunum yolu enfeksiyonudur [3]. Bireyin karşılaştığı mikroorganizmaya karşı oluşturduğu antikorlar, nöron yapısını moleküler düzeyde taklit mekanizması ile etkileyip çapraz reaksiyona girerek GBS'ye neden olur [4]. Progresyonu değişken olan GBS'de erken klinik belirtiler genellikle alt ekstremitelerde simetrik güç kaybı ile başlayıp üst ekstremitelere, yüze ve orofarengeal kaslara yayılır.…”
unclassified
“…Establishing a diagnosis for Guillain-Barré syndrome can be difficult, particularly in pediatrics, where rare unusual presentations occur, such as acute respiratory distress at the beginning. 13 24 Making an early diagnosis is challenging due to the treatments that consist in the rapid administration of intravenous immunoglobulin or plasma exchange. 25 …”
mentioning
confidence: 99%
“…[8][9][10][11][12] Establishing a diagnosis for Guillain-Barré syndrome can be difficult, particularly in pediatrics, where rare unusual presentations occur, such as acute respiratory distress at the beginning. [13][14][15][16][17][18][19][20][21][22][23][24] Making an early diagnosis is challenging due to the treatments that consist in the rapid administration of intravenous immunoglobulin or plasma exchange. 25 The authors present the case of a 7-year-old boy with an atypical and severe Guillain-Barré syndrome, and the authors describe all the challenges that the authors encountered to establish a diagnosis and for the medical management of the patient.…”
mentioning
confidence: 99%